Desiccation and rehydration in the lichen Cladonia convoluta monitored by laser scanning microscopy - Sass, László (Acta Biologica Szegediensis, 2002)
Changes in chlorophyll fluorescence emission from the lichen Cladonia convoluta were followed by imaging techniques. We compared fluorescence images of both the green (cortex) and the gray (fungal) side of the lichen at various stages of dessication and re-watering. Confocal laser scanning microscopy made the imaging of fluorescence from individual algal colonies possible inside the lichen, under the cortex in a non-invasive way.